Obtaining Patents for Innovative Products Designed by Nursing Faculty Members in Taiwan - Chien-Lin Kuo, Fen-Ching Tsai, Ya-Lie Ku, Man-Hua Shen, Pei-Yu Lee, (International Journal of Innovative Research in Medical Science, 2017)
This paper introduces the process of obtaining patents for innovative products. From 2014 to 2015, to enhance the ability of nursing faculty members to investigate products designed through nursing practicum projects, the principal investigator of this study formed a study community with the objectives of sharing innovative product designs developed by nursing teachers and instructing faculty members in how to research products. In addition, to obtain patents for the products, a patent expert was invited to guide the community members in the process of patent application. The following four innovative products were designed by nursing teachers in Taiwan: a medical toolbox, movement device with switching step and step function, multifunctional helmet, and catheter bag skirt.